1992
DOI: 10.1177/019459988910700606.1
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and pathogenesis of paranasal sinus mycoses

Abstract: In a prospective study, 50 cases of paranasal sinus mycoses were diagnosed in 2 years out of 119 clinically suspected patients from north India. Young men from rural areas were most commonly afflicted. Patients with paranasal sinus mycoses could be grouped in three clinical varieties: noninvasive, 31; invasive, 17; allergic, 2. Maxillary and ethmoid were the common sinuses concurrently involved in these patients, whereas sphenoid and frontal sinuses were also affected in invasive variety. Aspergillus flavus (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(85 citation statements)
references
References 14 publications
7
75
3
Order By: Relevance
“…In Western countries, A. fumigatus is the most important Aspergillus species that causes invasive aspergillosis and aspergilloma. On the other hand, A. flavus is the most common one associated with human disease in our locality and in other Asian countries (2,22). In our previous study, we demonstrated that A. flavus is responsible for causing 38% whereas A. fumigatus is responsible for causing only 19% of invasive mold diseases in bone marrow transplant recipients.…”
Section: Discussionmentioning
confidence: 48%
“…In Western countries, A. fumigatus is the most important Aspergillus species that causes invasive aspergillosis and aspergilloma. On the other hand, A. flavus is the most common one associated with human disease in our locality and in other Asian countries (2,22). In our previous study, we demonstrated that A. flavus is responsible for causing 38% whereas A. fumigatus is responsible for causing only 19% of invasive mold diseases in bone marrow transplant recipients.…”
Section: Discussionmentioning
confidence: 48%
“…flavus is more likely to be recovered from the upper respiratory tract than any other Aspergillus species (Chakrabarti et al, 1992;Hussain et al, 1995;Iwen et al, 1997;Kennedy et al, 1997;Panda et al, 1998). Clinical presentations of Aspergillus rhinosinusitis include acute and chronic invasive, chronic granulomatous and noninvasive syndromes (Hope et al, 2005).…”
Section: Rhinosinusitismentioning
confidence: 99%
“…Florid granulomatous inflammation is the histological hallmark of this condition. Interestingly, almost all reports come from the Sudan (Milosev et al, 1969;Gumaa et al, 1992;Yagi et al, 1999), Saudi Arabia (Alrajhi et al, 2001) and the Indian subcontinent (Chakrabarti et al, 1992;Ramani et al, 1994;Panda et al, 2004). There are a limited number of reports in the USA, which appear to affect almost exclusively African-Americans (Currens et al, 2002).…”
Section: Rhinosinusitismentioning
confidence: 99%
See 1 more Smart Citation
“…On basis of these reports it was postulated that young adult males who commonly go to the field in a hot, dry climate sustain frequent mucosal injuries of paranasal sinuses and acquire the agent from the field. [9] The incidence of paranasal sinus mycoses (fungal sinusitis) is significantly higher in Sudan, Saudi Arabia and south western states of USA and north India, which have hot and dry climate. North India has been identified as an endemic zone of paranasal sinus mycoses.…”
Section: Introductionmentioning
confidence: 99%